1982
DOI: 10.1136/gut.23.6.532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine on gastric mucosal blood flow and acid secretion.

Abstract: SUMMARY The effects of an intravenous infusion of nicotine at a dose of 2.5, 5.0, 7*5, or 100 ,g kg-'h-' on pentagastrin-stimulated gastric mucosal blood flow and acid secretion were investigated in eight healthy male non-smokers. Each dose was tested in two males. Gastric neutral red clearance served as a measure of mucosal blood flow. Nicotine reduced volume secretion, acid secretion, and neutral red clearance in a dose dependent manner. In five healthy male smokers smokinf of five cigarettes per two hours i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In the previous study, we have already observed that subcutaneous nitotine caused a decrease in the plasma IM and O-DM-IM con centrations after oral IM, which was similar to the effects of cigarette smoke exposure, and that nicotine did not cause such an effect after intravenous IM (10). Accordingly, the decreasing effects caused by nicotine and cigarette smoke exposure may have involved re tardation of IM absorption from the gastrointestinal tract, i.e., being mediated by a reduction of gastric mucosal blood flow (12) and/or an inhibition of gas trointestinal motility (11). On the other hand, as consti tuents other than nicotine in the gaseous phase of cigarette smoke, carbon monoxide, carbon dioxide, nit rogen oxides, ammonia, volatile sulfur and nitrogen containing compounds and so on were also determined (13).…”
mentioning
confidence: 59%
“…In the previous study, we have already observed that subcutaneous nitotine caused a decrease in the plasma IM and O-DM-IM con centrations after oral IM, which was similar to the effects of cigarette smoke exposure, and that nicotine did not cause such an effect after intravenous IM (10). Accordingly, the decreasing effects caused by nicotine and cigarette smoke exposure may have involved re tardation of IM absorption from the gastrointestinal tract, i.e., being mediated by a reduction of gastric mucosal blood flow (12) and/or an inhibition of gas trointestinal motility (11). On the other hand, as consti tuents other than nicotine in the gaseous phase of cigarette smoke, carbon monoxide, carbon dioxide, nit rogen oxides, ammonia, volatile sulfur and nitrogen containing compounds and so on were also determined (13).…”
mentioning
confidence: 59%
“…Clinical studies showed that smoking may stimulate [25][26][27][28] , inhibit [29,30] or have no effect [31,32] on gastric acid secretion. Such disparity between studies may be explained, in part, by the differences in nicotine content and number of cigarettes used, and by the lack of adequate controls due to marked individual variability of basal gastric secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of an intravenous infusion of nicotine at a dose 2.5 -10 μ g/kg per h on pentagastrin -stimulated gastric mucosal blood fl ow and acid secretion were studied in healthy male non -smokers. Nicotine reduced volume secretion, acid secretion, and Neutral Red clearance in a dose -dependent manner [21] . A similar change was seen in healthy male smokers smoking fi ve cigarettes per 2 h. PGF 2 α , a cyclooxygenase product with vascular effect on a submucosal microcirculation, and thromboxane ( Tx )B 2 , a potent platelet aggregator and vasoconstrictor, play an important role in the mucosal blood circulation.…”
Section: Gastric Mucosal Blood Flowmentioning
confidence: 99%